The relative importance of group-level effects on the performance of German companies - Steffen Brenner; Olaf Bunke; Bernd Droge; Joachim Schwalbach (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2001)
We examine the impact of performance groups on the estimation of the relative importance of firm, industry and other effects on corporate performance. Performance groups comprise firms from the same industry with a similar performance over a longer period of time. We present a statistical method which improves the procedure of variance decomposition by allowing firm effects and the interacting effects of firms and time to be unified into the group effects. Applied to a German data set of 219 companies observed over a period of eleven years (1987-1997) it appears that the majority of the firms can be ascribed to performance groups. The variance proportion of the group effects is about one half of the non-grouped firm effects. They explain about 17.9 percent of the total variance of the returns.
urn:nbn:de:kobv:11-10051126
Keywords: 330